Teknik Membangun Nilai dan Perencanaan Produk dalam Perspektif Manajemen Pemasaran Syariah: Kajian Pustaka - Khairul Anwar A, Syahrul (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2026)
This study examines the challenges in value creation within Islamic marketing, which is often dominated by symbolic approaches and has not fully reflected the substantive integration of Islamic values in halal business practices. The research aims to explain techniques for building value and their relationship with halal product planning based on the principles of maqashid sharia. Using a qualitative method through an analytical literature review of eighteen reputable journal articles and supporting academic sources, this study synthesizes conventional and Islamic marketing theories. The findings indicate that value creation in Islamic marketing is not only oriented toward material benefits but also highlights moral and spiritual values such as honesty, fairness, and blessing, which shape ethical business conduct. Product planning in the Islamic context must go through stages of idea development, innovation, halal verification, and educational value communication to ensure both welfare and business sustainability. This study proposes a conceptual model integrating value creation and product planning as a strategy for developing Islamic competitive advantage. The implications enrich the literature on Islamic marketing and provide practical guidance for halal industry practitioners in designing strategies that generate economic value while fulfilling religious and ethical responsibilities. Keywords: Islamic marketing, value creation, product planning.